Preparation method of flame-retardant thermal conductive fabric for fire alarm and product thereof
By depositing phytic acid-doped graphene oxide on silk fabrics, a flame-retardant thermally conductive fabric is formed, and the resistance conversion characteristics of graphene oxide are used to provide fire alarm signals, which solves the problems of graphene oxide's flammability and poor stability, and achieves the early stage Fire alarm and increase alarm duration.
Patent Information
- Application Number
- CN202411446145.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-24
AI Technical Summary
Existing graphene oxide is prone to flammability under high temperature or flame conditions, unable to provide early fire alarm signals, and poor thermal oxidation stability, resulting in limited application in the fire protection field.
The phytic acid is mixed with graphene oxide solution, and the mixture is prepared by stirring and sonication, and immersed on silk fabric to form a flame-retardant thermally conductive fabric, which uses the resistance conversion characteristics of graphene oxide at high temperature to provide fire alarm Signal.
This method can issue an alarm within 1 second when it is attacked by flames. The more graphene oxide is used, the longer the alarm lasts. It can last for 648 seconds at 25mL, which solves the problem of flammability and poor stability of graphene oxide. , improves the responsiveness and performance of fire alarm sensors.
Smart Images

Figure CN119177560A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional material preparation, and in particular relates to a preparation method of a flame-retardant and thermally conductive fabric for fire alarm and a product thereof. Background Art
[0002] With the development of society, natural fibers, polymer materials and their products are widely used in all aspects of human life. Although they decorate the living environment and improve the quality of life, their own flammability is potentially dangerous. Most of these materials have low ignition points and are prone to fire. Fire accidents not only aggravate the safety of human life and health, affect people's normal life, social and economic development, but also have an adverse impact on the atmosphere and ecological balance. -
[0003] Therefore, developing effective fire prevention methods is a major global challenge; current fire prevention and disaster reduction methods mainly include flame retardant technology, fire extinguishing technology and fire detection or alarm technology.
[0004] Graphene oxide (GO) consists of graphene oxide sheets, the basal plane of which is mainly modified by epoxy and hydroxyl groups, and the edges are modified by carbonyl and carboxyl groups. GO is non-conductive at room temperature, but when it encounters high temperatures or burns, the high temperature generated by the flame can remove the oxygen-containing groups in graphene oxide, turning it from a non-conductive state to a conductive state. This temperature-induced resistance conversion property of GO has brought huge space for its application in the field of fire protection, and can be used to provide effective fire alarm signals. In recent years, new fire early warning sensors based on the resistance change caused by the thermal reduction of GO under high temperature or flame conditions have attracted widespread attention.
[0005] Although graphene has excellent properties, its thermal oxidation stability is poor due to the presence of residual oxygen functional groups and defects, and GO is easily burned in air and cannot provide early fire alarm signals. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a flame retardant thermally conductive fabric for fire alarm.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a flame retardant thermal conductive fabric for fire alarm, comprising:
[0010] The phytic acid and the graphene oxide solution are mixed, stirred, and ultrasonically treated to obtain a mixed solution;
[0011] The mixed solution is immersed in silk fabric, phytic acid and graphene oxide are deposited on the surface of the silk fabric, and then dried to obtain flame-retardant and thermally conductive fabric for fire alarm;
[0012] Wherein, the concentration of the graphene oxide solution is 8 to 10 mg / mL;
[0013] The ratio of phytic acid to graphene oxide solution is 1 g: 10-25 mL.
[0014] As a preferred embodiment of the preparation method of the present invention, the ratio of phytic acid to graphene oxide solution is 1 g: 20-25 mL.
[0015] As a preferred solution of the preparation method of the present invention, the silk fabric comprises flame-retardant silk fabric.
[0016] As a preferred embodiment of the preparation method of the present invention, the preparation method of the flame retardant silk fabric comprises:
[0017] The cross-linking agent EH is mixed with phytic acid to prepare a flame retardant finishing liquid;
[0018] The pH value of the flame retardant finishing liquid was adjusted to 3 with sodium carbonate solution, and the silk fabric was immersed in the finishing liquid, immersed in a water bath at 40°C for 1 h with a bath ratio of 1:30, then immersed and rolled, dried at 80°C for 3 min, baked at 120°C for 2 min, washed with water, and dried at 80°C to obtain the flame retardant fabric.
[0019] As a preferred embodiment of the preparation method of the present invention, the flame retardant finishing liquid, wherein the concentration of the crosslinking agent EH is 3wt%, and the concentration of phytic acid is 25wt%.
[0020] As a preferred embodiment of the preparation method of the present invention, the ultrasonic treatment is performed for 30 to 40 minutes.
[0021] As a preferred embodiment of the preparation method of the present invention, the ratio of phytic acid to graphene oxide solution is 1 g:20 mL.
[0022] As a preferred embodiment of the preparation method of the present invention, the ratio of phytic acid to graphene oxide solution is 1 g:25 mL.
[0023] Another object of the present invention is to overcome the deficiencies in the prior art and provide a flame retardant, thermally conductive fabric for fire alarm.
[0024] Another object of the present invention is to overcome the deficiencies in the prior art and provide a flame retardant thermally conductive fabric for use in the preparation of a fire alarm.
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention provides a method for preparing a flame-retardant thermally conductive fabric for fire alarm, wherein phytic acid (PA) doped with graphene oxide (GO) is deposited on the surface of flame-retardant silk. When the amount of phytic acid (PA) is 1 g and the amount of graphene oxide (GO) is greater than 10 mL, an alarm can be triggered in about 1 second when attacked by flame, and the more graphene oxide is used, the longer the alarm lasts. When the amount is 25 mL, the alarm of the LS-PA-GO fabric can last up to 648 seconds.
[0027] (2) The flame-retardant thermally conductive fabric prepared by the present invention with flame-retardant textile material as the substrate can be used as a fire alarm sensor, which overcomes the defect of graphene itself being fragile after deposition, while improving the responsiveness of the alarm. Improving the alarm performance provides new ideas for the development of fire alarm sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0029] Figure 1 The infrared spectra of the silk prepared in Examples 1 and 2 of the present invention and the film prepared in Comparative Example 1 are shown.
[0030] Figure 2 1 and 1 are thermogravimetric diagrams of the original silk and the flame-retardant thermally conductive fabric in the embodiments of the present invention, wherein a is the thermogravimetric diagram of the original silk and b is the thermogravimetric diagram of the flame-retardant thermally conductive fabric.
[0031] Figure 3 This is the infrared spectrum of the film prepared in Comparative Example 1 of the present invention before and after combustion.
[0032] Figure 4 The alarm reaction time and alarm duration diagram of the S-PA-GO of the present invention, where (a) 1gPA+10mLGO, (b) 1gPA+15mL GO, (c) 1gPA+20mL GO, and (d) 1gPA+25mL GO.
[0033] Figure 5 In the present invention, 1 g of phytic acid and different amounts of graphene oxide (10 mL, 15 mL, 20 mL, 25 mL) solution are deposited on the surface of silk fabric to form a thermally conductive fabric prepared by silk / phytic acid / graphene oxide, wherein: (a) 1 gPA+10 mLGO, (b) 1 gPA+15 mL GO, (c) 1 gPA+20 mL GO, and (d) 1 gPA+25 mL GO.
[0034] Figure 6 In the present invention, 1 g of phytic acid and different amounts of graphene oxide (10 mL, 15 mL, 20 mL, 25 mL) are deposited on the surface of a flame-retardant silk fabric to form a flame-retardant silk / phytic acid / graphene oxide to prepare a flame-retardant thermally conductive fabric, wherein: (a) 1 gPA+10 mL GO; (b) 1 gPA+15 mL GO; (c) 1 gPA+20 mL GO; (d) 1 gPA+25 mL GO.
[0035] Figure 7 In the present invention, 1g phytic acid PA was evaporated and induced to deposit with 10mL, 15mL, 20mL, and 25mL graphene oxide GO on the surface of flame-retardant silk to prepare flame-retardant fire alarm fabrics, including: (a) 1gPA+10mL GO; (b) 1gPA+15mL GO; (c) 1gPA+20mL GO; (d) 1gPA+25mL GO.
[0036] Figure 8 The PA-GO film prepared by evaporation-induced deposition of graphene oxide (10 mL, 15 mL, 20 mL, 25 mL) when the phytic acid concentration is 1 g is used for fire alarm performance test, where (a) 1g PA + 10 mL GO, (b) 1g PA + 15 mL GO, (c) 1g PA + 20 mL GO, (d) 1g PA + 25 mL GO. DETAILED DESCRIPTION
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0040] Infrared spectrum test in the embodiment of the present invention:
[0041] Fourier transform attenuated total reflection infrared spectroscopy (ATR-FTIR) was used for analysis; the sample was analyzed from 400 cm -1 Scan up to 4000cm -1 , drawn by origin8.0 software.
[0042] Thermogravimetric analysis in the embodiments of the present invention:
[0043] The samples were analyzed by thermogravimetric differential thermal analyzer to analyze the thermal stability and weight loss rate of silk fabrics.
[0044] The graphene oxide in the embodiment of the present invention was purchased from Suzhou Carbonfeng Technology, with a concentration of 10 mg / mL, a sheet diameter of 10-50 um, a monolayer rate of >90%, and an oxidation degree of 36%; other raw materials are all common commercially available products.
[0045] Example 1
[0046] This embodiment provides a method for preparing a flame-retardant thermally conductive fabric for fire alarm, the main steps of which are:
[0047] (1) 1 g of phytic acid was mixed with 20 mL of graphene oxide solution, and the mixture was stirred for 10 min. The mixture was then ultrasonicated in an ultrasonic oscillator for 30 min to obtain a mixed solution. The concentration of the graphene oxide solution was 10 mg / mL.
[0048] (2) pouring the mixed solution into a surface dish containing ordinary silk fabric, and allowing it to deposit on the surface of the silk fabric;
[0049] (3) drying at 60°C to obtain silk / phytic acid / graphene oxide, namely, the flame retardant and thermally conductive fabric S-PA-GO.
[0050] Example 2
[0051] This embodiment provides a method for preparing a flame-retardant thermally conductive fabric for fire alarm, the main steps of which are:
[0052] (1) preparing a flame retardant finishing liquid by mixing crosslinking agent EH (3 wt %) and phytic acid (25 wt %);
[0053] The pH value of the flame retardant finishing liquid is adjusted to 3 by adding water to anhydrous sodium carbonate to prepare a sodium carbonate solution (25 wt%);
[0054] Take 1g of silk fabric and immerse it in the finishing liquid with a bath ratio of 1:30 in a water bath at 40℃ for 1h, then immerse and roll it, bake it at 80℃ for 3min, bake it at 120℃ for 2min, wash it with water, and dry it at 80℃ to obtain the flame retardant fabric.
[0055] (2) 1 g of phytic acid was mixed with 20 mL of graphene oxide solution, and the mixture was stirred for 10 min. The mixture was then ultrasonicated in an ultrasonic oscillator for 30 min to obtain a mixed solution. The concentration of the graphene oxide solution was 10 mg / mL.
[0056] (3) pouring the mixed solution into a surface dish containing the flame retardant fabric, and allowing it to deposit on the surface of the flame retardant silk fabric;
[0057] (4) drying at 60°C to obtain silk / phytic acid / graphene oxide, i.e., flame retardant and thermally conductive fabric LS-PA-GO.
[0058] Comparative Example 1
[0059] The amount of graphene oxide was fixed at 20 mL. 1 g of phytic acid was added to 20 mL of graphene oxide GO solution (10 mg / mL) and stirred thoroughly for 10 min.
[0060] Then, the dispersed solution was placed in an ultrasonic oscillator for 30 minutes of ultrasonication. After the ultrasonication, the dispersed solution was poured into a watch glass and dried at 60°C to obtain a PA-GO membrane.
[0061] The infrared spectra of the silk obtained in Example 1 and Example 2 and the film obtained in Comparative Example 1 are shown in Figure 1 , it can be seen that in the infrared spectrum of the original silk sample, 3413cm -1 The absorption peak that appears corresponds to the stretching vibration of OH, at 1646 cm -1 The absorption peak represents the stretching vibration of the C=O bond in the peptide bond, at 1514 cm -1 The absorption peak represents the bending vibration of the NH bond in the plane, at 1227 cm -1 The absorption peak that appears represents the stretching vibration of the CN bond;
[0062] In the infrared spectrum of PA-GO film, 3427 cm -1 and 1352cm -1 The absorption peaks at 1630 cm-1 correspond to the stretching vibration of OH. -1 The absorption peak that appears represents the skeleton vibration of the reduced graphene oxide;
[0063] In addition, at 1721cm -1 The absorption peak is the characteristic peak of C=O, at 1113cm -1and 953cm -1 The absorption peaks that appear are attributed to the stretching vibration peaks of C-OH and CO.
[0064] In the infrared spectrum of silk / phytic acid / graphene oxide, 3445 cm -1 The absorption peak at 1635 cm -1 The absorption peak that appears represents the stretching vibration of the C=O bond in the peptide bond. The infrared spectrum of PA-GO after evaporation-induced deposition on silk does not change much, proving that it has little effect on the structure of silk.
[0065] The infrared spectrum of flame retardant silk / phytic acid / graphene oxide is 3438 cm -1 The absorption peak at 1634 cm -1 The absorption peak that appears represents the stretching vibration of the OPO unit, 1062cm -1 The absorption peak that appears belongs to the stretching vibration peak of COC. The infrared spectrum of PA-GO after evaporation-induced deposition on flame-retardant silk does not change much, proving that it has little effect on the structure of silk and has the characteristics of phytic acid and graphene oxide.
[0066] Thermogravimetric graphs of silk as is and flame retardant and thermally conductive fabrics are shown in Figure 2 , where a is the thermogravimetric graph of the original silk, and b is the thermogravimetric graph of the flame-retardant thermal conductive fabric. It can be observed that the curves have dropped to varying degrees at 0-300℃, which is mainly due to the evaporation of moisture in the fabric after the temperature rises, causing the curve change. The thermogravimetric curve of silk has dropped significantly during 300-600℃, and the thermogravimetric curve of the flame-retardant thermal conductive fabric has dropped significantly during 250-500℃. The reason may be that the macromolecular chain of the fabric has cracked, resulting in an increase in weight loss; after 600℃, it began to smoothen, indicating that the silk fabric was completely decomposed above 600℃. By observing that the mass change of the original silk is 80%, the residual mass is less than 5%, while the mass change of the flame-retardant thermal conductive fabric is 50%, the residual mass is 20%, the mass change decreases, and the residual amount increases, indicating that the stability of the silk fabric is significantly improved after the flame-retardant thermal conductive treatment.
[0067] The infrared spectra of the film obtained in Comparative Example 1 before and after combustion are shown in Figure 3 It can be seen that in the infrared spectrum of PA-GO film, 3427 cm -1 and 1352cm -1 The absorption peaks at 1630 cm-1 correspond to the stretching vibration of OH. -1 The absorption peaks that appear are the skeleton vibrations of reduced graphene oxide; in addition, at 1721 cm -1The absorption peak is the characteristic peak of C=O, at 1113cm -1 and 953cm -1 The absorption peaks that appear are attributed to the stretching vibration peaks of C-OH and CO. In the infrared spectrum after combustion, 3444 cm -1 The absorption peak at 1634 cm -1 The absorption peak that appears represents the skeleton vibration of graphene, 1004cm -1 The absorption peak that appears belongs to the stretching vibration peak of COC. Comparison of the two infrared spectra fully demonstrates that graphene oxide forms graphene after high-temperature reduction, thus having conductivity.
[0068] Comparative Example 2
[0069] (1) 1 g of phytic acid was mixed with 10 mL of graphene oxide solution, and the mixture was stirred for 10 min. The mixture was then ultrasonicated in an ultrasonic oscillator for 30 min to obtain a mixed solution. The concentration of the graphene oxide solution was 10 mg / mL.
[0070] (2) pouring the mixed solution into a surface dish containing ordinary silk fabric, and allowing it to deposit on the surface of the silk fabric;
[0071] (3) drying at 60°C to obtain silk / phytic acid / graphene oxide, namely the flame retardant and thermally conductive fabric S-PA-GO-10.
[0072] Comparative Example 3
[0073] (1) 1 g of phytic acid was mixed with 15 mL of graphene oxide solution, and the mixture was stirred for 10 min. The mixture was then ultrasonicated in an ultrasonic oscillator for 30 min to obtain a mixed solution. The concentration of the graphene oxide solution was 10 mg / mL.
[0074] (2) pouring the mixed solution into a surface dish containing ordinary silk fabric, and allowing it to deposit on the surface of the silk fabric;
[0075] (3) drying at 60°C to obtain silk / phytic acid / graphene oxide, namely the flame retardant and thermally conductive fabric S-PA-GO-15.
[0076] Comparative Example 4
[0077] (1) 1 g of phytic acid was mixed with 25 mL of graphene oxide solution, and the mixture was stirred for 10 min. The mixture was then ultrasonicated in an ultrasonic oscillator for 30 min to obtain a mixed solution. The concentration of the graphene oxide solution was 10 mg / mL.
[0078] (2) pouring the mixed solution into a surface dish containing ordinary silk fabric, and allowing it to deposit on the surface of the silk fabric;
[0079] (3) drying at 60°C to obtain silk / phytic acid / graphene oxide, i.e., flame retardant and thermally conductive fabric S-PA-GO-25.
[0080] S-PA-GO alarm response time and alarm duration refer to Figure 4 , among them, (a) 1gPA+10mL GO; (b) 1gPA+15mL GO; (c) 1gPA+20mL GO; (d) 1gPA+25mL GO;
[0081] Figure 4 The fire alarm fabrics were prepared by evaporation-induced deposition of 1g phytic acid PA and 10mL, 15mL, 20mL, and 25mL graphene oxide GO on silk. The alarm reaction time was about 1s. When the graphene oxide concentration was 10mL, the alarm duration was only 164s. When the concentration reached 15mL, the alarm duration increased to 215s. When the concentration reached 20mL, the alarm duration increased to 328s. When the concentration increased to 25mL, the alarm duration was 602s. When the GO concentration was greater than 20mL, the alarm duration of the prepared S-PA-GO was lower than that of PA-GO. It may be that as the burning time increases, the silk fabric burns, thereby accelerating the burning and breaking of the S-PA-GO film, making the alarm duration shorter than that of PA-GO. It can be seen that in order to increase the alarm duration, it is necessary to flame retard the fabric to reduce the burning of the fabric.
[0082] By evaporation-induced deposition method, 1 g of phytic acid and different amounts of graphene oxide solution (10 mL, 15 mL, 20 mL, 25 mL) were deposited on the surface of silk fabric to form silk / phytic acid / graphene oxide. The thermal conductive fabric was prepared by Figure 5 , among which, (a) 1gPA+10mL GO, (b) 1gPA+15mL GO, (c) 1gPA+20mL GO, (d) 1gPA+25mL GO, when PA / GO was deposited on the surface of silk fabric, it was found that its rule was close to that of direct deposition in a culture dish. That is, when the amount of graphene oxide GO was 10mL, PA-GO was thinner and formed a thin film directly on the surface of the fabric, which was not easy to fall off. As the amount of GO increased, the formability of PA-GO improved, but it would cause the curling of the fabric, mainly because the GO content increased and the thickness of the film deposited on the silk surface increased. As the amount of GO increased to 25mL, the PA-GO film deposited on the silk surface separated from the silk, and the formability decreased, which was not conducive to the use of thermally conductive fabrics.
[0083] Comparative Example 5
[0084] (1) 1 g of phytic acid was mixed with 10 mL of graphene oxide solution, and the mixture was stirred for 10 min. The mixture was then ultrasonicated in an ultrasonic oscillator for 30 min to obtain a mixed solution. The concentration of the graphene oxide solution was 10 mg / mL.
[0085] (2) pouring the mixed solution into a surface dish containing the flame retardant fabric, so that it is deposited on the surface of the flame retardant silk fabric;
[0086] (3) drying at 60°C to obtain silk / phytic acid / graphene oxide, i.e., flame retardant and thermally conductive fabric LS-PA-GO-10.
[0087] Comparative Example 6
[0088] (1) 1 g of phytic acid was mixed with 15 mL of graphene oxide solution, and the mixture was stirred for 10 min. The mixture was then ultrasonicated in an ultrasonic oscillator for 30 min to obtain a mixed solution. The concentration of the graphene oxide solution was 10 mg / mL.
[0089] (2) pouring the mixed solution into a surface dish containing the flame retardant fabric, so that it is deposited on the surface of the flame retardant silk fabric;
[0090] (3) drying at 60°C to obtain silk / phytic acid / graphene oxide, i.e., flame retardant and thermally conductive fabric LS-PA-GO-15.
[0091] Comparative Example 7
[0092] (1) 1 g of phytic acid was mixed with 25 mL of graphene oxide solution, and the mixture was stirred for 10 min. The mixture was then ultrasonicated in an ultrasonic oscillator for 30 min to obtain a mixed solution. The concentration of the graphene oxide solution was 10 mg / mL.
[0093] (2) pouring the mixed solution into a surface dish containing the flame retardant fabric, so that it is deposited on the surface of the flame retardant silk fabric;
[0094] (3) drying at 60°C to obtain silk / phytic acid / graphene oxide, i.e., flame retardant and thermally conductive fabric LS-PA-GO-25.
[0095] 1 g of phytic acid and different amounts of graphene oxide (10 mL, 15 mL, 20 mL, 25 mL) were deposited on the surface of flame-retardant silk fabric to form flame-retardant silk / phytic acid / graphene oxide to prepare flame-retardant thermally conductive fabrics, see Figure 6 , among them, (a) 1gPA+10mL GO; (b) 1gPA+15mL GO; (c) 1gPA+20mL GO; (d) 1gPA+25mL GO;
[0096] from Figure 6It was found that when the amount of graphene oxide GO was 10mL, the fabric curled and wrinkled after drying, and the PA-GO film was unevenly distributed on the fabric surface. This may be because the feel and softness of the fabric were affected to a certain extent after the flame retardant finishing. At the same time, the amount of GO was small and could not be evenly spread on the fabric surface. During the drying process, the fabric was made to have a certain degree of compactness, which eventually led to curling and wrinkling of the fabric. However, as the amount of GO increased, the fabric became relatively flat, which was the opposite of the direct deposition on the silk surface.
[0097] The flame-retardant silk has a certain hardness. As the amount of GO increases gradually, the thickness of the film deposited on the silk surface increases. The active hydroxyl groups in the phytic acid grafted on the fabric have a certain interaction with the hydroxyl groups in the PA-GO film (the hydroxyl groups in the phytic acid and the hydroxyl groups in the graphene oxide), which makes the PA-GO film fit the flame-retardant silk better, which is conducive to the use of fire alarm fabrics.
[0098] 1g of phytic acid PA was evaporation-induced deposited on the flame-retardant silk surface with 10mL, 15mL, 20mL, and 25mL of graphene oxide GO, respectively, to prepare flame-retardant fire alarm fabrics, see Figure 7 , among them, (a) 1gPA+10mL GO; (b) 1gPA+15mL GO; (c) 1gPA+20mL GO; (d) 1g PA+25mL GO;
[0099] It can be seen that the alarm reaction time is about 1s. When the graphene oxide concentration is 10mL, the alarm duration is only 191s. When the concentration reaches 15mL, the alarm duration increases to 311s. When the concentration reaches 20mL, the alarm duration increases to 473s. When the concentration is 25mL, the alarm duration is 648s.
[0100] Comparative Example 8
[0101] On the basis of Comparative Example 1, when the phytic acid concentration was 1 g, the PA-GO film prepared by evaporation-induced deposition with changing the amount of graphene oxide (10 mL, 15 mL, 20 mL, 25 mL) was used for fire alarm performance test.
[0102] See also Figure 8 , among them, (a) 1gPA+10mL GO, (b) 1gPA+15mL GO, (c) 1g PA+20mL GO, (d) 1gPA+25mL GO;
[0103] It can be seen that the change in graphene oxide concentration has little effect on the alarm reaction time, which is about 1s, but has a greater impact on the alarm duration. When the graphene oxide concentration is 10mL, the alarm duration is only 149s. When the concentration reaches 15mL, the alarm duration increases to 165s. When the concentration reaches 20mL, the alarm duration increases to 433s. When the concentration increases to 25mL, the alarm duration is 619s, indicating that the increase in the amount of graphene oxide can effectively increase the alarm duration. This is mainly because when graphene oxide is exposed to high temperature or flame, oxygen-containing functional groups (hydroxyl, carboxyl, epoxy resin, etc.) and water molecules are removed to form reduced graphene oxide, which has excellent conductivity. However, when the PA-GO film burns to a certain extent and breaks, it is equivalent to the closed circuit being disconnected, making the alarm unable to be powered on, thereby stopping the alarm.
[0104] A comprehensive analysis of the three fire alarm products, PA-GO membrane, S-PA-GO and LS-PA-GO, shows that the overall alarm duration of LS-PA-GO is better than that of PA-GO membrane and S-PA-GO. The relevant data are shown in Summary Table 1.
[0105] Table 1
[0106]
[0107] Comparative Example 9
[0108] Resistance test:
[0109] The resistance of the residues after combustion of PA-GO membrane, S-PA-GO, and LS-PA-GO when the GO concentration was 10 mL, 15 mL, 20 mL, and 25 mL is shown in Table 2. It can be observed that with the increase of GO concentration, the resistance of the product decreases continuously, so the conductive performance is better.
[0110] A comprehensive analysis of the three post-combustion products, PA-GO membrane, S-PA-GO and LS-PA-GO, revealed that the overall resistance of LS-PA-GO is lower than that of PA-GO membrane and S-PA-GO, and its overall conductive performance is better than that of PA-GO membrane and S-PA-GO.
[0111] Table 2 Measured resistance of PA-GO film, S-PA-GO and LS-PA-GO (kΩ)
[0112]
[0113] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a flame-retardant thermally conductive fabric for fire alarm, characterized in that: include, The phytic acid and the graphene oxide solution are mixed, stirred, and ultrasonically treated to obtain a mixed solution; The mixed solution is immersed in silk fabric, phytic acid and graphene oxide are deposited on the surface of the silk fabric, and then dried to obtain flame-retardant and thermally conductive fabric for fire alarm; Wherein, the concentration of the graphene oxide solution is 8 to 10 mg / mL; The ratio of phytic acid to graphene oxide solution is 1 g: 10-25 mL.
2. The preparation method according to claim 1, characterized in that: The ratio of the phytic acid to the graphene oxide solution is 1 g: 20-25 mL.
3. The preparation method according to claim 1 or 2, characterized in that: The silk fabric comprises a flame retardant silk fabric.
4. The preparation method according to claim 3, characterized in that: The flame retardant silk fabric, the preparation method thereof comprises: The cross-linking agent EH is mixed with phytic acid to prepare a flame retardant finishing liquid; The pH value of the flame retardant finishing liquid was adjusted to 3 with sodium carbonate solution, and the silk fabric was immersed in the finishing liquid, immersed in a water bath at 40°C for 1 h with a bath ratio of 1:30, then immersed and rolled, dried at 80°C for 3 min, baked at 120°C for 2 min, washed with water, and dried at 80°C to obtain the flame retardant fabric.
5. The preparation method according to claim 4, characterized in that: In the flame retardant finishing liquid, the concentration of the crosslinking agent EH is 3wt%, and the concentration of the phytic acid is 25wt%.
6. The preparation method according to claim 1, characterized in that: The ultrasonic treatment, wherein the ultrasonic treatment time is 30 to 40 minutes.
7. The preparation method according to claim 1, characterized in that: The ratio of the phytic acid to the graphene oxide solution is 1 g:20 mL.
8. The preparation method according to claim 3, characterized in that: The ratio of the phytic acid to the graphene oxide solution is 1 g:25 mL.
9. The flame retardant thermally conductive fabric obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the flame-retardant thermally conductive fabric according to claim 9 in the preparation of a fire alarm.
